2015
DOI: 10.1200/jco.2014.58.1751
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Castration-Resistant Prostate Cancer Trials

Abstract: All progress is precarious, and the solution of one problem brings us face to face with another problem.-Martin Luther King Jr 1(pp82-83) Disparities in health care delivery and outcomes are complex and longstanding. Many such disparities derive from limited access to health care, socioeconomic barriers, and cultural differences-each of which can result in minorities receiving suboptimal care, and ultimately in inferior outcomes. Recently published SEER data again underscore the undeniable disparities in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…Reasons behind the larger representation of African Americans in the current study are unknown, given historically African Americans have been under-represented in clinical trials [8,27]. One contributing factor may be the time frame of the PROCEED registry (first subject first visit 27 January 2011 and last subject last visit 17 January 2017), a period of significant change in advanced prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Reasons behind the larger representation of African Americans in the current study are unknown, given historically African Americans have been under-represented in clinical trials [8,27]. One contributing factor may be the time frame of the PROCEED registry (first subject first visit 27 January 2011 and last subject last visit 17 January 2017), a period of significant change in advanced prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Still, TCGA can be commended for their enrollment of racial minorities that has been far more successful than many clinical trial efforts. 5 …”
Section: Discussionmentioning
confidence: 99%
“…However, our study population was 25% non-white compared to 10% in similar matching studies and was able to reach a higher proportion of minority populations [ 22 ]. Spratt and colleagues reported that African American men comprise about 3.3% of phase III randomized clinical trials in prostate cancer [ 23 ]. Our study found that 5.1% of participants who used the matching tool when the Google AdWords campaign was live identified as African American.…”
Section: Discussionmentioning
confidence: 99%
“…When implemented at scale and over a longer duration, such interventions may help to better balance demographic representation among trial participants. While prostate cancer clinical trials continue to underrepresent racial/ethnic minorities [ 23 ], these findings suggest that underrepresented minorities are actively seeking online health information. Therefore, this study serves as an important rationale for future investigators to develop novel Internet-based interventions to deliver health information to a diverse population of men with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%